Axial response of high-resolution microendoscopy in scattering media - Koucky, Michael H. (Optical Society of America, 2013)
High-resolution microendoscopy (HRME) uses epi-fluorescence imaging with a coherent fiber-optic bundle to enable in vivo examination of cellular morphology. While the HRME platform has recently gained popularity as a simple alternative to confocal endomicroscopy, the axial response of HRME in thick, scattering tissue has yet to be described quantitatively. These details are important because when analyzing images collected by HRME, out-of-focus light may affect the accuracy of quantitative parameters such as nuclear-to-cytoplasm ratio, which has been proposed as a diagnostic indicator of dysplasia or cancer. In this study we investigated the imaging properties of the HRME system by using phantoms simulating scattering tissue with fluorescently labeled nuclei. We directly compared HRME imaging with confocal endomicroscopy in phantoms and in vivo human tissue. HRME images defocused (deep) objects with apparent diameters and intensity levels that are in agreement with a simple geometric model. Out-of-focus nuclei contribute a relatively low, uniform background level to images which neither leads to the erroneous appearance of large nuclei from deep layers, nor prevents accurate imaging of superficial nuclei with high contrast.